Ameliorating motor performance and quality of life in Parkinson’s disease: a comparison of deep brain stimulation and focused ultrasound surgery - Liang, Mingqian; Hou, Le; Liang, Jinjun; Bao, Shengyong (Frontiers in Neurology, 2025)
IntroductionDeep brain stimulation (DBS) and magnetic resonance-guided focused ultrasound surgery (MRgFUS) have emerged as valuable treatment options for Parkinson’s disease (PD) with drug-resistant symptoms. However, comparative studies of various DBS targets and MRgFUS are still limited.MethodsWe reviewed three databases for trials on the effects of DBS or MRgFUS on PD patients, focusing on motor performance and quality of life (QoL). A frequentist network meta-analysis was conducted to estimate the treatment effects.ResultsThere were 39 trials in this study, comprising 3,002 patients. In the off-phase, subthalamic nucleus_DBS (STN_DBS [SMD, −0.94; 95%CI, −1.40 to −0.48]) significantly improved the UPDRS-III Total score compared to medication treatment alone (MT). In the on-phase, STN_DBS (SMD, −0.83; 95%CI, −1.13 to −0.53), internal globus pallidus_DBS (GPi_DBS [SMD, −0.80; 95%CI, −1.20 to −0.40]), and STN_Focused Ultrasound (STN_FUS [SMD, −1.83; 95%CI, −2.97 to −0.68]) significantly improved the UPDRS-III Total score. Regarding QoL, STN_DBS (SMD, −0.75; 95% CI, −1.46 to −0.05) and GPi_DBS (SMD, −0.58; 95% CI, −0.96 to −0.21) demonstrated better outcomes compared to MT. The SUCRA plot indicated that the top three treatments for UPDRS-III Total score in the off-phase were STN_FUS (79.6%), STN-GPi_DBS (73.7%), and STN_DBS (69.1%). In the on-phase, the top three treatments were STN_FUS (95.7%), STN_DBS (69.6%), and GPi_DBS (66.9%). Regarding QoL, GPi_DBS (77.2%) ranks first, followed by STN_DBS (67.3%), STN_FUS (56.9%) ranks third.ConclusionSTN_DBS, GPi_DBS, and STN_FUS have exhibited efficacy in ameliorating motor performance and enhancing QoL in PD patients. Nevertheless, as a potential alternative to STN_DBS with comparable efficacy, STN-FUS may serve as another treatment option.